FEATURES OF PUBLIC ADMINISTRATION IN ENSURING ENVIRONMENTAL SAFETY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The environment has always been the source of the energy of life. It is from naturalresources that peoples receive a resource to continue their existence. This article discusses topicalissues of environmental protection and environmental safety, the role of public administration andtheir ways in solving these problems.
Keywords: state, management, environmental safety, environmental protection, quality of life.